Tuning the Structure of Nylon 6,6 Electrospun Bundles to Mimic the Mechanical Performance of Tendon Fascicles - Sensini, Alberto; Santare, Michael H.; Eichenlaub, Emily; Bloom, Ellen; Gotti, Carlo; Zucchelli, Andrea; Cristofolini, Luca (Frontiers in Bioengineering and Biotechnology, 2021)
Tendon and ligament injuries are triggered by mechanical loading, but the specific mechanisms are not yet clearly identified. It is well established however, that the inflection and transition points in tendon stress-strain curves represent thresholds that may signal the onset of irreversible fibrillar sliding. This phenomenon often results in a progressive macroscopic failure of these tissues. With the aim to simulate and replace tendons, electrospinning has been demonstrated to be a suitable technology to produce nanofibers similar to the collagen fibrils in a mat form. These nanofibrous mats can be easily assembled in higher hierarchical levels to reproduce the whole tissue structure. Despite the fact that several groups have developed electrospun tendon-inspired structures, an investigation of the inflection and transition point mechanics is missing. Comparing their behavior with that of the natural counterpart is important to adequately replicate their behavior at physiological strain levels. To fill this gap, in this work fascicle-inspired electrospun nylon 6,6 bundles were produced with different collector peripheral speeds (i.e. 19.7 m s−1; 13.7 m s−1; 7.9 m s−1), obtaining different patterns of nanofibers alignment. The scanning electron microcopy revealed a fibril-inspired structure of the nanofibers with an orientation at the higher speed similar to those in tendons and ligaments. A tensile mechanical characterization was carried out showing an elastic-brittle biomimetic behavior for the higher speed bundles with a progressively more ductile behavior at slower speeds. Moreover, for each sample category the transition and the inflection points were defined to study how these points can shift with the nanofiber arrangement and to compare their values with those of tendons. The results of this study will be of extreme interest for the material scientists working in the field, to model and improve the design of their electrospun structures and scaffolds and enable building a new generation of artificial tendons and ligaments.